FAKTOR-FAKTOR PENENTU AUDIT DELAY DI INDONESIA: STUDI META ANALYSIS - Handarudigdaya JK; Tri Wdiyastuti; Adi Wiratno; Iskandar Ahmaddien (UPPM Akademi Komunitas Semen Indonesia, 2019)
This study aims to examine the determinants of audit delay in Indonesia, using Meta Analysis. Where Meta analysis is a standard statistical method that serves to synthesize results from individual studies that have